Three-Dimensional Reconstruction of Impact Crater Morphology During the Impact Process - Yizhuo Zheng; Wanqing Sun; Hui Yang; Ran Li (IEEE Access)
Employing continuous medium three-dimensional reconstruction technology, this study explores the morphological evolution of crater surfaces during impact processes in the field of particle technology, investigating numerical variations and evolution rates in two dimensions. The results show that three-dimensional reconstruction effectively addresses dynamic surface measurement challenges with an accuracy error within the 0.2mm to 0.5mm range. The central depth, edge height, and diameter of the impact crater exhibit an initial increase with time, followed by a turning point within the same time range, eventually stabilizing. The distribution of crater morphology evolution rates aligns with the study of particle motion states at different times within the crater. Furthermore, a comparison with changes in particle velocity at specific locations reveals a consistent variation rate in the center depth of the impact crater with the trend of particle velocity changes. This suggests that the surface morphology of the impact crater can be determined by aggregating particle velocities radially, thereby constructing its overall features.